PERAN JIWA KEWIRAUSAHAAN DALAM MENGEMBANGKAN UMKM KERIPIK ROSSA - Muhammad Ridho Pratama Saputra; Vonny Tiara (CV. Adiba Aisha Amira, 2026)
Entrepreneurship is one of the things that is most important for a country. Entrepreneurship can grow the economy and community welfare. This research’s aim is to further research and analyze the entrepreneurial spirit in developing Rossa Chips in Bandar Lampung City. Qualitative research methods is used in this research where research activities are carried out through critical analysis with the presentation of scientific sentences. This research was conducted at the Small and Medium Enterprises (SMEs) Kripik Rossa in Bandar Lampung City. The informant in this research is the owner of the Kripik Rossa business. The results of this research show that the entrepreneurial spirit basically exists within each human being and that potential needs to be channeled through the business that is founded. Strengthening the entrepreneurial spirit will have the impact of strengthening entrepreneurial behavior. The role of an entrepreneurial spirit can increase the formation of business independence.